Estimation of Concentration Polarization Using the Combined Film theory/ Spiegler-Kedem Model and Empirical Correlation - Khalaf, Taha Yaseen (Nahrain University College of Engineering Journal, 2008)
At a given operating pressure and in a given apparatus, concentration polarization results in an increase in the effective osmotic pressure of the feed solution on the membrane surface, a consequent decrease in the effective pressure ( P ) for fluid flow across the membrane, and progressive changes in the mass transfer coefficient, product rate, and solute separation along the length of the membrane in the direction of feed flow. The problem then is to predict theeffect of concentration polarization on solute separation and on predict rate, under specified experimental condition. In the present work, the reverse osmosisexperiments were conducted in a spiral wound model to get separation data using a NaCl-water system up to 2500 ppm and cellulose acetate membrane.The purpose of this paper is to predict and analyze the concentration polarization using a combined film theory model and empirical correlation. Therefore, the results of the experiments show that the concentration polarization affected when using different models